Public-social partnership for enhancing the value of human capital in local production systems. Lodz Region case study - Przygodzki, Zbigniew (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
Inter-sectoral cooperation is one the most important elements of contemporary, place-based policy. Deriving from the conditions of the environment, also the global one, local actors should join their forces by investing in the resources determining today’s’ development – knowledge and human capital – in the most effective way. However, internal national or regional conditions, very often do not allow for efficient adaptation of development mechanisms, even when they have been already tested in other places. By narrowing the area of analysis to the relationships between territorial self-government and non-governmental organisations, this paper is an attempt to answer the question on what scale, in the Polish conditions, public-social partnerships are being built and what is their scope. Analysis concerns the institutions involved in the investment in knowledge and human capital, operating in the region of Lodz.